Identification of Municipal Solid Waste Landfill Sites using the GIS and AHP Multicriteria decision analysis: A case of the urban municipality of Dédougou (Burkina Faso) - Kafando, Halidou; Roland, Koueta Téré; Ouedraogo, Blaise; Jeremi, Rouamba (Geographica Pannonica, 2026)
Sustainable management of municipal solid waste is a major challenge for developing countries, where rapid population growth and accelerated urbanization are increasing waste production and pressure on landfill sites. Selecting suitable landfill sites is a complex task that requires consideration of multiple environmental, geological, topographical and anthropogenic factors in order to minimize impacts on public health and the environment. This study focuses on the urban commune of Dédougou and proposes an approach combining GIS and the Analytic Hierarchy Process (AHP) to identify optimal municipal waste landfill sites. The data used includes groundwater depth, distance from built-up areas, distance from watercourses, slope, altitude, land use and cover, soil types, geological formations, and distance from road networks. Each factor was standardized, weighted according to Thomas L. Saaty’s 1977 AHP scale, and integrated into the GIS to produce a landfill suitability map. The results indicate a classification of areas into five categories: very unfavorable (9.29%), unfavorable (23.55%), moderately favorable (27.25%), favorable (39.88%) and very favorable (0.06%). The weightings assigned reveal that groundwater depth (0.386), proximity to built-up areas (0.232) and distance from watercourses (0.131) are the most influential factors. The final map shows that suitable and very suitable sites are mainly located on the northern and north-western outskirts of the urban commune of Dédougou, while the central areas are largely unsuitable for landfills.